A Potential Role of the Inferior Frontal Gyrus and Anterior Insula in Cognitive Control, Brain Rhythms, and Event-Related Potentials - Tops, Mattie; Boksem, Maarten A. (Frontiers in Psychology, 2011)
In the present paper, we review evidence for of a model in which the inferior frontal gyrus/anterior insula area (IFG/AI) is involved in elaborate attentional and working memory processing and we present the hypothesis that this processing may take different forms and may have different effects, depending on the task at hand: 1. it may facilitate fast and accurate responding, or 2. it may cause slow responding when prolonged elaborate processing is required to increase accuracy of responding, or 3. it may interfere with accuracy and speed of next-trial (for instance, post-error) performance when prolonged elaborate processing interferes with processing of the next stimulus. We present our viewpoint that ventrolateral corticolimbic control pathways, including the IFG/AI, and mediodorsal corticolimbic control pathways, including dorsal anterior cingulate cortex areas, play partly separable, but interacting roles in adaptive behaviour in environmental conditions that differ in the level of predictability: compared to dorsal feed-forward control, the ventral corticolimbic control pathways implement control over actions through higher responsiveness to momentary environmental stimuli. This latter control mode is associated with an attentional focus on stimuli that are urgent or close in time and space, while the former control mode is associated with a broader, more global focus in time and space. Both control pathways have developed extensively through evolution, and both developed their own “cognitive controls”, such that neither one can be properly described as purely “cognitive” or “emotional”. We discuss literature that suggests that the role of IFG/AI in top-down control is reflected in cortical rhythms and event-related potentials. Together, the literature suggests that the IFG/AI is an important node in brain networks that control cognitive and emotional processing and behavior.